Representations on Patagonian native people in school textbooks. 1886-1940 (Quinto Sol, 2013)
The Patagonia, like a mythical land and their native inhabitants, has been analyzed through different studies. Nevertheless, its representation through the textbooks is a topic scarcely studied. Based on a corpus of fourteen textbooks, belonging to State and Salesian schools, we intend to analyze two specific representations on Patagonian natives: 1) the native as “savage” and “enemy” of the “civilization” in a “empty” space, a “desert” and 2) the native “paleontologizado”, without history, in a natural space with productive potential. The representations are linked to two ideas related to the political ones of the State on the Patagonia: one with the territorial level: the idea of “desert” and “emptiness” and other one, with that of its inhabitants: the idea of “savagery” and “barbarism”, such ideas being useful to legitimize the conquest and the extermination of its native inhabitants. In the textbooks the didactic transposition operated overlaping our categories of analysis.
Keywords: Textbooks; Patagonia; native peoples; representations